Artefactual nanoparticle activation of the inflammasome platform: in vitro evidence with a nano-formed calcium phosphate. (May 2015) - Pele, Laetitia; Haas, Carolin T; Hewitt, Rachel; Faria, Nuno; Brown, Andy; Powell, Jonathan
Aim: To determine whether in vitro experimental conditions dictate cellular activation of the inflammasome by apatitic calcium phosphate nanoparticles.Material & methods: The responses of blood-derived primary human cells to in situ -formed apatite were investigated under different experimental conditions to assess the effect of aseptic culture, cell rest and duration of particle exposure. Cell death and particle uptake were assessed, while IL-1β and caspase 1 responses, with and without lipopolysaccharide prestimulation, were evaluated as markers of inflammasome activation.Results: Under carefully addressed experimental conditions, apatitic nanoparticles did not induce cell death or engage the inflammasome platform, although both could be triggered through artefacts of experimentation.Conclusion: In vitro studies often predict that engineered nanoparticles, such as synthetic apatite, are candidates for inflammasome activation and, hence, are toxic. However, the experimental setting must be very carefully considered as it may promote false-positive outcomes. Original submitted 13 September 2013; Revised submitted 6 March 2014